Patient harboring a novel PIK3CA point mutation after acquired resistance to crizotinib in an adenocarcinoma with ROS1 rearrangement: A case report and literature review. Issue 6 (28th August 2017) - Xu, Chun‐wei; Wang, Wen‐xian; Huang, Rong‐fang; He, Cheng; Liao, Xing‐hui; Zhu, You‐cai; Du, Kai‐qi; Zhuang, Wu; Chen, Yan‐ping; Chen, Gang; Fang, Mei‐yu
Abstract : ROS1 rearrangement occurs in 1–2% of non‐small cell lung cancer (NSCLC) cases. These patients would benefit from treatment with the anaplastic lymphoma kinase inhibitor, crizotinib; however, resistance to crizotinib inevitably develops in such patients despite an initial response. The mechanism of acquired resistance to crizotinib in patients with NSCLC with ROS1 rearrangement has not yet been identified. Herein, we report a case of a 66‐year‐old woman diagnosed with adenocarcinoma. PCR revealed no EGFR or ALK mutations. After the patient underwent several rounds of chemotherapy, crizotinib was administered. The disease explosively progressed six months later. A novel PIK3CA gene point mutation (p.L531P) was detected by next generation sequencing. This case is the second report of bypass activation conferred crizotinib resistance in a patient with NSCLC with ROS1 ‐rearrangement, but is the first to confirm that activation of the mTOR signaling pathway leads to acquired crizotinib resistance.